Non-HDL Cholesterol Versus LDL Cholesterol as a CVD Risk Factor in Diabetic Subjects - Saiedullah, M; Begum, S; Hayat, S; Kamahuddin, SM; Rahman, MR; Khan, MAH (Journal of Bangladesh College of Physicians and Surgeons, 2014)
Objective: Serum low density lipoprotein (LDL) cholesterol is considered as the primary target of lipid lowering therapy and non-high density lipoprotein (HDL) cholesterol is the recommended second target. Recent studies claimed that non-HDL cholesterol is a better predictor of cardiovascular diseases (CVD) than LDL cholesterol. In this study we aimed to compare non-HDL cholesterol and LDL cholesterol as a CVD risk factor in confirmed diabetic subjects. Materials and methods: In this cross-sectional observational study, 1042 confirmed diabetic subjects selected randomly were included. HbA1c Results: In the total subjects, 767 (74%) subjects had LDL cholesterol > 100 mg/dL and 822 (79%) subjects had non- HDL cholesterol > 130 mg/dL. HbA1c values were different (p<0.02) in five groups and showed upward trend (p<0.01). All the lipid parameters studied were significantly different in five groups (p<0.0001) and TC, TG and non-HDL cholesterol showed upward trend (p<0.0001), but HDL cholesterol and LDL cholesterol showed downward trend (p<0.0001). Odds ratio (OR) of likelihood of risk individuals regarding non-HDL cholesterol compared to LDL cholesterol were 0.50 (p<0.001), 1.32 (p>0.05), 2.96 (p<0.001), 6.49 (p<0.001) and 9.37 (p<0.001) for TG concentrations of up to 150 mg/dL, 151-200 mg/dL, 201-250 mg/dL, 251-300 mg/dL and 301-400 mg/dL respectively with relative risk of 0.60, 1.24, 2.43, 4.83, 5.10. Conclusion: LDL cholesterol is a better tool for the detection of high-risk individuals than non-HDL cholesterol at TG concentration up to 150 mg/dL, whereas non-HDL cholesterol is better than LDL cholesterol at TG concentration above 200 mg/dL as a CVD risk factor. DOI: http://dx.doi.org/10.3329/jbcps.v31i4.21004 J Bangladesh Coll Phys Surg 2013; 31: 199-203